Effects of Sex, Age, and Habitat on Northern Bobwhite Spring Dispersal Patterns - M. Patrick Cook; Richard G. Hamrick; John P. Carroll (National Quail Symposium Proceedings, 2017)
Information on northern bobwhite (Colinus virginianus) dispersal patterns is crucial for implementing effective management strategies. Researchers have examined bobwhite dispersal, but information on how habitat affects dispersal patterns is lacking. We examined the effects of habitat, sex, and age on bobwhite spring dispersal patterns in a southern Georgia agricultural landscape during 2002-2003. Of 101 birds used in our analyses, 29.7% (4.6 SE) dispersed an average of 1,835m (194 SE). We fit 9 logistic regression models to predict bobwhite dispersal probability. The selected best model (Akaike weight [ω] = 0.58) included age, proportions of closed-canopy pine within winter home ranges (CCPN), and an age*CCPN interaction term. Adults with higher proportions of closed-canopy pine within their winter home range were more likely to disperse (ß = 0.18, 0.06 SE). Because of greater experience, adults may perceive habitat differently than juveniles, which could influence adult tendency to disperse. However, a significant portion of birds from both age classes will likely disperse every spring, regardless of habitat quality. Although dispersal may allow bobwhite populations to persist in fragmented landscapes, efforts to increase bobwhite populations at the local scale are hindered if emigration exceeds immigration. Therefore, it is important to consider landscape quality and management unit size when determining which areas are most likely to respond to management and the proper management strategy needed to achieve bobwhite population objectives.
Keywords: age; closed-canopy pine; Colinus virginianus; dispersal; Georgia; habitat; metapopulation; northern bobwhite; scale; sex